Some Dynamic Phenomena in the Leontief Model of Reversely Lagged Type - Nikaido, Hukukane (Review of Economic Studies, 1962)
Journal Article Some Dynamic Phenomena in the Leontief Model of Reversely Lagged Type Get access Hukukane Nikaidô Hukukane Nikaidô Osaka Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 29, Issue 4, October 1962, Pages 313–323, https://doi.org/10.2307/2296307 Published: 01 October 1962